Power Transition and Hedging Strategies: Latin America in the China and United States Rivalry - Quiliconi, Cintia (2026)
Introduction: Strategic competition between China and the United States is changing the global order and redefining the foreign policy options for Latin American countries. This rivalry reduces the region's room for maneuver. Objective: This article analyzes how this strategic competition constrains the room for maneuver of Latin American countries, with the aim of identifying the strategies adopted in response to this rivalry and the conditions under which it is possible to preserve a degree of autonomy. Methodology: The study draws on two theoretical frameworks: power transition theory and the literature on hedging strategies, in order to characterize how Latin American countries manage risks and opportunities. The article uses a qualitative methodology and analyzes three case studies in strategic sectors: infrastructure (the Port of Chancay in Peru), technology (5G deployment in Brazil and Mexico), and security/defense (China-Latin America cooperation and US responses, the ECU-911 case). Conclusions: We argue that although rivalry tends to restrict regional room for maneuver, several Latin American countries have implemented hedging strategies that enable them to benefit from both powers without rigidly aligning with either. Latin American agency persists, but it is increasingly conditioned by the interregnum of the current transitional moment in the international order.